The Correlation Between Olfactory Test and Hippocampal Volume in Alzheimer's Disease and Mild Cognitive Impairment Patients: A Meta-Analysis - Su, Ming-Wan; Ni, Jing-Nian; Cao, Tian-Yu; Wang, Shuo-Shi; Shi, Jing; Tian, Jin-Zhou (Frontiers in Aging Neuroscience, 2021)
Background: Previous studies have reported that olfactory identification deficits may be the earliest clinical features of Alzheimer's disease (AD). However, the association between odor identification and hippocampal atrophy remains unclear. Objective: This meta-analysis quantified the correlation between odor identification test scores and hippocampal volume in AD. Method: A search of the PUBMED, EMBASE, and WEB OF SCIENCE databases was conducted from January 2003 to June 2020 on studies with reported correlation coefficients between olfactory identification score and hippocampal volume in patients with amnestic AD or mild cognitive impairment (MCI). The quality of the studies was assessed using the Newcastle-Ottawa quality assessment scale (NOS). Pooled r-values were combined and computed in R studio. Results: Seven of 627 original studies on AD/MCI using an olfactory identification test (n = 902) were included. A positive correlation was found between hippocampal volume and olfactory test scores (r = 0.3392, 95% CI: 0.2335–0.4370). Moderator analysis showed that AD and MCI patients were more profoundly correlated than normal controls (AD: r = 0.3959, 95% CI: 0.2605–0.5160; MCI: r = 0.3691, 95% CI: 0.1841–0.5288; NC: r = 0.1305, 95% CI: −0.0447–0.2980). Age difference and patient type were the main sources of heterogeneity in this analysis. Conclusion: The correlation appears to be more predominant in the cognitive disorder group (including MCI and AD) than in the non-cognitive disorder group. Age is an independent factor that affects the severity of the correlation during disease progression. The mildness of the correlation suggests that olfactory tests may be more accurate when combined with other non-invasive examinations for early detection. Systematic Review Registration:https://inplasy.com/, identifier INPLASY202140088.